Successful treatments of plasma exchange, hemodialysis, immunosuppresive agents and dimethylsulfoxide in a case of myeloma kidney - MIZUNO, MASAO; FUJISHIRO, TOSHIIAKA; FUNAHASHI, NAOKI; KOJIMA, KUNIYOSHI; OGAWA, TADASHI; YANAI, TOSHIYUKI; KAWASHIMA, SHIRO; MURAI, SUMIKO; HASEGAWA, HIROSHI (The Japanese Journal of Nephrology, 1987)
The case is a 57-years-old man, who was examined with chief complaints of anorexia and lumbago and hospitalized for renal failure of unknown origin together with azotemia and hyperkalemia. Bence-Jones protein λ type confirmed in both the blood and the urine suspected amybid kidney or myeloma kidney. Light and electron microscopic findings of renal biopsy showed tubular degeneration, intratubuloluminal protein cast, syncytium cell and no amyloid deposition. Additional bone marrow aspiration confirmed abundant atypical plasma cells. Thus, the case was diagnosed as Bence-Jones 2 type myeloma kidney. In addition to chemotherapy after several treatments of hemodialysis and plasma exchange, dimethyl sulfoxide was given p. o. and i. v. in hopes of improving renal function via elution of the Bence-Jones protein from the tubular lumen. As a result, decreases in Bence-Jones protein in both the blood and the urine, apparent improvement of renal function and of general conditions were obtained. Since then the patient has been doing well without hemodialysis.